ANALISIS PENILAIAN KINERJA PEGAWAI PADA BALAI TEKNIK PENYEHATAN LINGKUNGAN PERMUKIMAN SURABAYA - Lestari, Wahyu; Sulandari, Susi (Journal of Public Policy and Management Review, 2017)
Performance appraisal is an activity carried out management / supervisors to assess and measure also evaluate the performance of employees for the work they do. Performance appraisal could be used to determine the weaknesses and strengths of employees. The weaknesses and strengths used as foundation to improve the weaknesses and strengthen the advantages in order to improve productivity and employee development. Performance appraisal is intended to determine the level of employee performance. This study was to describe how the level of employee performance at Balai Teknik Penyehatan Lingkungan Permukiman Surabaya and What the indicators which are the weak levels of employee performance appraisal at Balai Teknik Penyehatan Lingkungan Permukiman Surabaya with quantitative descriptive. The data analyze is used an average or mean, mode, median and frequency distribution and graphs. Informants in this study are civil servants of Balai Teknik Penyehatan Lingkungan Permukiman Surabaya and data collected through questionnaires, observation, and documentation to provide information about employee performance. The results of this study explains that the level of employee performance Balai Teknik Penyehatan Lingkungan Permukiman Surabaya are good and indicators that are weak and need to increase with the lowest average is an indicator of time, teamwork and some sub indicators are indicators of quantity and discipline. Based on these results, the performance level civil servants at Balai Teknik Penyehatan Lingkungan Permukiman Surabaya are good. There are some suggestions that can be done such as socialization of time management to all employees and also employee need more focus and concentration to their work, more understand the importance of teamwork with superiors, subordinates, colleagues and other organization, so that the work can be done properly and according to expectations of organization.